Calcium glycerophosphate and fluoride affect the pH and inorganic composition of dual-species biofilms of Streptococcus mutans and Candida albicans - Cavazana, Thamires Priscila [UNESP]; Hosida, Thayse Yumi [UNESP]; Sampaio, Caio [UNESP]; de Morais, Leonardo Antônio [UNESP]; Monteiro, Douglas Roberto; Pessan, Juliano Pelim [UNESP]; Delbem, Alberto Carlos Botazzo [UNESP] (Elsevier, 2021)
Objectives: This study evaluated the influence of calcium glycerophosphate (CaGP), combined with or without fluoride (F), on the pH and concentrations of F, Ca, and P of dual-species biofilms of Streptococcus mutans and Candida albicans, with or without exposure to sucrose. Methods: The biofilms (n = 9) received three treatments (72, 78, and 96 h after the start of their formation) at three CaGP concentrations (0.125, 0.25, or 0.5%), with or without F at 500 ppm (as NaF). Solutions containing 500 and 1100 ppm F and artificial saliva were also tested as controls. Biofilm pH was measured, and the concentrations of F, Ca, P, and CaGP were determined (solid and fluid phases). In a parallel experiment, after the third treatment, the treated biofilms were exposed to a sucrose solution, and the pH of the medium, F, Ca, P, and CaGP was determined. Data were subjected to two-way ANOVA, followed by Fisher's LSD test (p < 0.05). Results: Treatment with CaGP and 500 ppm F led to the highest pH values and F and Ca concentrations in the biofilm biomass, both with and without sucrose exposure. CaGP without F led to higher Ca and P concentrations in the biofilm fluid. Conclusions: CaGP increased F, Ca, and P concentrations in the biofilm, and its presence promoted an increase in the pH of the medium, even after exposure to sucrose. Clinical significance: The present results elucidate the mechanism by which CaGP and F act on biofilms, further interfering with dental caries dynamics.
Keywords: Biofilms; Calcium glycerophosphate; Candida albicans; Fluoride; Phosphate; Streptococcus mutans